ADAPTASI BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DI DATARAN RENDAH MEDAN - Elisa Manora Sinaga; Eva Sartini Bayu; Isman Nuriadi Isman Nuriadi (Jurnal Agroekoteknologi, 2013)
Onionis one of the leading vegetable seed which has long cultivated. Demand onioncontinues to increase, so that production needs to be increased, where one attempts to do that is theuse of high yielding varieties. The availability of local varieties provide many options, it alsodecrease the use ofimported seeds, it is necessary to test the power of high yielding varieties inother areas.This research was aimed to select shallot varieties that able to adapt in Medan lowland.This research was conducted on level land in Simalingkar, Tuntungan District (± 25 meters abovesea) in June-September 2012. This research used Randomized Block Design (RBD) treatmentconsisting of five varieties are Katumi, Yellow, Sembrani variety, Medan and Tuk-Tuk variety, thetreatment was replicated four times. The data obtained were analyzed using analysis of variancefollowed by Duncan’s Multiple Range Test (DMRT). The results of showed that varietiessignificantly different with number of tillers, fresh weight plant sample, dry weight plant sample,tuber diameter, tuber height and tuber water loss and production. Of the five onion varieties testedshowed not significantly in variables plant height, number of leaves, harvest, fresh weight plant plotand dry weight plant plot.